2010
DOI: 10.1038/jid.2009.349
|View full text |Cite
|
Sign up to set email alerts
|

Possible Roles of IL-27 in the Pathogenesis of Psoriasis

Abstract: The immunological significance of IL-27 has been reported and discussed in various Th1/Th17-mediated inflammatory diseases. However, its importance in psoriasis is unknown. We investigated pathophysiological roles of IL-27 in psoriasis in this study. Serum IL-27 levels in psoriatic patients were significantly higher than those in healthy controls, and correlated with disease severity and serum IFN-gamma levels. An immunohistochemical analysis revealed the infiltration of IL-27-secreting cells in the papillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 37 publications
7
75
1
2
Order By: Relevance
“…We found higher IL-27 mRNA expression in lesional skin of psoriasis patients than in skin samples from healthy donors (Supplemental Fig. 1), according to previous data [19]. IL-27 expression was also above in asymptomatic skin from psoriasis patients, but this difference was not statistically significant.…”
Section: Galectin Expression Is Defective In Psoriatic Skinsupporting
confidence: 84%
“…We found higher IL-27 mRNA expression in lesional skin of psoriasis patients than in skin samples from healthy donors (Supplemental Fig. 1), according to previous data [19]. IL-27 expression was also above in asymptomatic skin from psoriasis patients, but this difference was not statistically significant.…”
Section: Galectin Expression Is Defective In Psoriatic Skinsupporting
confidence: 84%
“…However, the precise contribution of IL-27 to immune response, inflammation, and cancer is still poorly understood. On one hand, IL-27 has proinflammatory effects through the induction of CXCL10 in macrophages in inflammatory skin disorders (43). However, IL-27 may limit the proinflammatory and immune-enhancing activities of IL-18 in the skin through IL-18BP induction (33) and may dampen autoimmunity, as Il27 À/À mice were more susceptible to experimental autoimmune encephalomyelitis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-27 promotes a proinflammatory type 1 response by priming human primary keratinocytes, macrophages or inflammatory dendritic epidermal cells for IL-6, TNF␣, CXCL10, and IL-23 production, respectively. IL-27 is therefore significantly involved in initiating and driving the chronic phase of inflammatory skin diseases (1)(2)(3)7). Interestingly, as shown by Owaki et al (9) for CD4 ϩ T cells, the STAT3-responsive molecule SOCS3 3 is also induced by IL-27.…”
Section: Suppressor Of Cytokine Signaling (Socs)3 Belongs To a Familymentioning
confidence: 72%
“…Recently, we reported that IL-27 was found to be expressed in the chronic (Th1-dominated) but not in the acute phase of eczema (Th2-dominated) (2). In addition, Shibata et al (1) found an infiltration of IL-27-secreting cells in psoriatic skin lesions. In both cases it may act as a strong proinflammatory mediator able to maintain Th1 cell response in the epidermal compartment.…”
Section: Discussionmentioning
confidence: 94%